The Effect of a Health Education Intervention on Jordanian Participants' Colorectal Cancer Knowledge, Health Perceptions, and Screening Practices. Issue 3 (May 2018) - Abuadas, Fuad H.; Petro-Nustas, Wasileh J.; Abuadas, Mohammad H.
Abstract : Background: Globally, colorectal cancer (CRC) is the second and third most commonly diagnosed cancer in women and men, respectively. Objectives: The aim of this study is to test the effectiveness of a health education intervention on the current level of Jordanians' CRC knowledge, health perceptions, and screening practices. Methods: A convenience sampling method was used to recruit a sample of 197 average-risk Jordanian adults aged 50 to 75 years. The sample was collected from outpatient departments of Jordan University and Al-Basheer Hospitals in Amman. This study used quasi-experimental design, and a rolling enrollment method was implemented to randomly assign the participants into intervention and control groups. Results: Baseline results indicated that Jordanian average-risk participants were not well informed about CRC and screening recommendations. One-fourth perceived themselves to be susceptible to CRC. About one-third comprehended the seriousness of CRC, most recognized the benefits of CRC screening, and fewer than half believed there were barriers preventing them from participating in CRC screening. Four weeks after intervention implementation, there was a significantly higher level of knowledge, as well as increased susceptibility and severity perceptions, screening via fecal occult blood test, and intentions to undergo screening via colonoscopy or sigmoidoscopy. Conclusion: The findings support the implementation of a health education intervention as an effective way to enhance levels of knowledge and promote positive health perceptions regarding CRC and screening recommendations. Implications for Practice: This study may provide Jordanian and other nurses with a theory-based educational intervention to improve the quality of nursing care and reduce costs.